2023
DOI: 10.1038/s41467-023-38416-6
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic conformational switching underlies TFIIH function in transcription and DNA repair and impacts genetic diseases

Abstract: Transcription factor IIH (TFIIH) is a protein assembly essential for transcription initiation and nucleotide excision repair (NER). Yet, understanding of the conformational switching underpinning these diverse TFIIH functions remains fragmentary. TFIIH mechanisms critically depend on two translocase subunits, XPB and XPD. To unravel their functions and regulation, we build cryo-EM based TFIIH models in transcription- and NER-competent states. Using simulations and graph-theoretical analysis methods, we reveal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…While many mutations in Core subunits therefore cause sensitivity to ultraviolet (UV) light, this is not the case for Kinase Module mutants. Recent structures (reviewed in (Yu et al, 2023)) show that the Kinase Module would block interactions between the Core Module and other NER factors. Therefore, TFIIH either enters into the NER complex as free Core Module, or the Kinase Module must dissociate soon after.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…While many mutations in Core subunits therefore cause sensitivity to ultraviolet (UV) light, this is not the case for Kinase Module mutants. Recent structures (reviewed in (Yu et al, 2023)) show that the Kinase Module would block interactions between the Core Module and other NER factors. Therefore, TFIIH either enters into the NER complex as free Core Module, or the Kinase Module must dissociate soon after.…”
Section: Resultsmentioning
confidence: 99%
“…Structures are available for free TFIIH complex, TFIIH incorporated into the PIC, and TFIIH as part of the NER machinery (reviewed in (Yu et al, 2023)). The Core Module has a roughly horseshoe shape, with the TFIIH ATPases, Ssl2/XPB and Rad3/XPD, at the two ends.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The DNA entry pore, formed by the Arch domain together with the FeS and the ATPase lobe 1 domains, plays an important role in helicase activity, damage verification and NER efficiency ( 64 , 73–79 ). Several studies have yielded a number of significant insights on the role of the Arch dynamics in XPD’s helicase activity ( 67 , 74 , 80 , 81 ). Ghoneim and Spies showed that, when DNA bound, the Arch domain undergoes thermally driven open-close transitions that slightly favor the closed state with CPD present ( 74 ).…”
Section: Discussionmentioning
confidence: 99%